Tea consumption and ovarian cancer risk: a case-control study in China - Zhang, Min; Binns, Colin; Lee, Andy (American Association for Cancer Research, 2002)
To investigate whether tea consumption has an etiological associationwith ovarian cancer, a case-control study was conducted in China during 1999–2000. The cases were 254 patients with histologically confirmed epithelial ovarian cancer. The 652 controls comprised 340 hospital visitors, 261 non-neoplasm hospital outpatients, and 51 women recruited from the community. Information on the frequency, type, and duration of tea consumption was collected by personal interview using a validated questionnaire. The risk of ovarian cancer for tea consumption was assessed using adjusted odds ratios based on multivariate logistic regression analysis, accounting for confounding demographic, lifestyle, and familial factors including hormonal status and family ovarian cancer. The ovarian cancer risk declined with increasing frequency and duration of overall tea consumption. The adjusted odds ratio was 0.39 for those drinking tea daily and 0.23 for those drinking tea for >30 years, compared with nontea drinkers. The dose response relationships were significant, and the inverse association with ovarian cancer was observed for green tea consumption. We concluded that increasing frequency and duration of tea drinking, especially green tea, can reduce the risk of ovarian cancer. However, the protective effects of black tea and Oolong tea need to be additionally investigated.